The effect of the Pressley model with various educational methods in teaching some basic football skills (Journal of the College of Basic Education, 2024)
The objectives of the thesis included designing educational units according to the Pressley model, using various educational means, to teach some basic skills in football, and identifying the effect of the Pressley model, using various educational means, teaching some basic skills in football, and identifying the superior effect of the two groups in post-tests, learning some basic skills in football. The researchers used the experimental method due to its suitability and research requirements and because it is the appropriate means to prove its hypotheses. The experimental research method was adopted and the experimental design was adopted for two independent groups of equal number, experimental and control. The researchers defined the research population as first-year students in the Department of Physical Education and Sports Sciences, College of Basic Education - Al-Mustansiriya University for the academic year 2023-2024, adults. Their number was 179 male and female students. The research sample was limited to males only because the subject of football was taught to males, and the number of them was 132 students. They were chosen in a systematic random way, which included 30 students who constituted 22.72% of the total male population, divided into two groups, each group consisting of (15) One student was chosen randomly to represent Hall 1, the experimental group, to which the Pressley model will be applied using the various educational methods under investigation, while Hall No. 3, the control group, will be applied to the prescribed curriculum and according to the method followed. The other 15 students were chosen to represent the sample on which the exploratory experiment will be conducted from Hall 6. The researchers proceeded to important procedures in the research, including their own tests. After that, the researchers conducted exploratory experiments, from which the scientific conditions for the skill tests were extracted, after which a pre-test was conducted for the two football skill groups. After that, the researchers prepared educational units according to the Pressley model using various educational means and included 12 One educational unit per week, and the time of the educational unit is 90 minutes, and the total time of the educational units is 10.80 minutes, according to the teaching system in the Department of Physical Education and Sports Sciences at the College of Basic Education, Al-Mustansiriya University, for football for first-stage students. After applying 12 educational units, the researchers conducted the post-test for the two groups. By tabulating the raw data and referencing it to modern scientific sources, research results were reached on which the two researchers based their most important conclusions, including the effect of educational units using the Pressley model supported by various educational methods on guiding students to be effective participants in the learning process by enhancing their interaction and motivation, and that the Pressley model works to Encouraging students to participate actively in the educational process, whether through group discussions, practical exercises, or problem solving. Among the most important recommendations are: Directing the attention of researchers and teachers to implementing educational units based on the Pressley model and supported by various educational methods, in order to enhance their students’ learning and increase their interaction and motivation.